Ecological anatomy of Some Hydrophytes in Nigeria - Jayeola, Adeniyi A.; Folorunso, Ezekiel A. (2014)
Structural features were studied in ten common hydrophytes from divergent groups, sampled from the Opa-Lake of Obafemi Awolowo University, Ile-Ife and the creeks of the River Ramos in Ogbotogbo Nigeria. Teh preponderance of parenchyma tissue is striking in all the species whereas specialized tissues such as treachery elements, sclerieds and fibres are scanty and restricted. Lacuna varies in size from as large 8000 - 11000 um in Scleria depressa to as small as 3 - 400 um in Onagraceae sp., Commelina diffusa, Ludwigia suffruticosa and Zebrina pendula. Presence of multicellular trichomes distinguishes Lemna pausicoststa and L. suffruticosa from the remaining species. Chloroplasts were observed in various regions of stems in other species except S. depressa. These attributes represent different degrees of adaptation to aquatic life and are widely convergent among aquatic groups. The observed structural similarity may be related to uniformity of the aquatic habitat. All the same, variation in characters show sufficient discontinuity to support separation of the species studied for taxonomic evaluation.